Study on the process parameters of delamination on novel madar/ramie fibers reinforced MgO nanoparticles blended epoxy matrix composite - Vinayagam Mohanavel; A. Thanikasalam; Thandavamoorthy Raja; M. Ravichandran; Manigandan Ayyar; Ranganathan Lakshmanan; Manzoore Elahi M. Soudagar (Results in Engineering)
The final assembly of composite parts often requires secondary techniques such as milling and drilling. This study aims to identify the most effective drilling parameters for a novel composite material reinforced with madar/ramie fibers, magnesium oxide filler particulates, and an epoxy matrix. Madar/ramie fibers offer significant benefits, including high tensile strength, biodegradability, and cost-effectiveness, making them an eco-friendly and sustainable choice for composite reinforcement. The study evaluates the impact of varying drill diameters (6, 8, and 10 mm), spindle speeds (500, 1000, and 1500 rpm), and feed rates (0.1, 0.2, and 0.3 mm/rev) on the drilling process. Using HSS drill bits, key factors such as thrust force, torque, and delamination were analyzed through Taguchi and Response Surface Methodology (RSM) to predict the optimal drilling parameters. The findings indicate that the hybrid madar/ramie composite exhibits minimal delamination at a drill diameter of 6 mm, a spindle speed of 1500 rpm, and a feed rate of 0.1 mm/rev. These optimal conditions enhanced the qualitative characteristics of drilled holes while reducing production costs. Experimental validation confirmed the composite's suitability for drilling operations and its endurance under ideal conditions.